In Vivo Evaluation of Antidepressant Potential of Temulawak (Curcuma xanthorriza Robb.) Ethanol Extract in Mus musculus - Virgilius, Raja David; Limbong, Zest Lively; Ginting, Jericho L. (Biology, Medicine, & Natural Product Chemistry, 2025)
Temulawak (Curcuma xanthorriza Roxb.) is a medicinal plant from the Zingiberceae family widely used in Indonesia for its various bioactives, including antiviral, antibacterial, and hepatoprotective properties. This research aims to evaluate the antidepressant potential of Curcuma xanthorriza ethanol extract in Mus musculus through in vivo testing. The extraction used the maceration method with 96% ethanol as a solvent, yielding 5.2504% extract. The primary bioactive compounds identified in the extract were terpenoids and curcuminoids, which are known for their neuroprotective and antidepressant effects. The antidepressant activity was assessed using the tail-suspension test (TST) and forced-swimming test (FST), with immobility time as the main parameter. Amitriptyline, a standard antidepressant, was used as a positive control, while sodium carboxymethylcellulose served as a negative control. The results showed that increasing doses of Curcuma xanthorriza extract significantly reduced immobility time, indicating an antidepressant-like effect. Statistical analysis revealed that the immobility time in mice treated with a 650 mg/Kg BW dose of Curcuma xanthorriza extract was not significantly different from the amitriptyline group, suggesting comparable efficacy. These findings highlight the potential of Curcuma xanthorriza ethanol extract as a natural antidepressant, warranting further investigation into its mechanisms and clinical applications.